Pengaruh Struktur Modal, Ukuran Perusahaan, Kepemilikan Institusional, Kepemilikan Terkonsentrasi dan Profitabilitas Terhadap Harga Saham Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 2014-2019 - Felicia Anggraeni; Diyan Lestari (UNIVERSITAS KALBIS, 2022)
This research aims to determine the effect of capital structure, firm size, institutional ownership, concentrated ownership, and profitability on the stock prices of food and beverage companies listed on the Indonesia Stock Exchange from 2014 to 2018. The sample of this research is food and beverage companies listed on the Indonesia Stock Exchange from 2014 to 2018 with a total of 17 companies as sample. The method of analysis in this research is panel regression. The result of this research indicate that capital structure doesn’t affect on stock prices, firm size doesn’t affect on stock prices, institutional ownership doesn’t affect on stock prices, concentrated ownership doesn’t affect on stock prices, and profitability proxied by return on asset affects the stock prices.